Theoretical Approach of Teaching Written Speech Methodology to The Language University Students - Turgunova Shakhnoza Tursunbayevna (Genius Journals, 2022)
The article discusses the process of formation of written communicative competence in the first year of a language university. It describes the construction of a written text based on the analysis of the psycholinguistic features of written speech in English; the principles of constructing a methodology for teaching written speech in the first year of a language university were determined; and also clarified the goals and content of teaching writing in the first year of a language university
Keywords: communicative competence; written text; content of teaching writing; language university